PERAN MEDIA PEMBELAJARAN INTERAKTIF DALAM MENGEMBANGKAN KETERAMPILAN ABAD 21 PADA SISWA KELAS TINGGI - Hati, Silvia Tabah; Karo, Karmila Br (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2025)
Abstract: Twenty-first century skills—critical thinking, creativity, communication, and collaboration—are essential for elementary students to navigate global challenges. This article examines how interactive learning media can support the development of these skills among upper-grade elementary students. Employing a literature review approach, the study analyzes findings from peer-reviewed journals, academic books, and previous research. Results indicate that integrating interactive media, particularly those utilizing information and communication technology (ICT), enhances student engagement and encourages meaningful, collaborative learning. Such media foster both cognitive and socio-emotional development by promoting active participation and real-world contextualization. Overall, interactive learning media play a vital role in creating adaptive and student-centered educational environments that align with 21st-century learning demands.““